فہمِ شریعت کے لیےمقاصد شریعت کی اہمیت اور علمائےکرام کے نظریات: The Importance of Maqasid al-Shariah in Understanding Islamic Law and the Perspectives of Islamic Scholars (Al-Aasar, 2025)
Islamic Shariah is a complete system sent by Allah for the well-being of humans in this world and the Hereafter. It includes worship, morals, social life, and daily dealings. Simply memorizing the rules or following them without understanding their purpose does not give a true understanding of Shariah. Understanding this purpose is called the understanding of Shariah (Fahm-e-Shariah). Through this understanding, a person can know the wisdom behind every rule and the objectives it aims to achieve. The objectives of Shariah are meant to ensure basic welfare and well-being in human life. They protect five main areas: religion, life, intellect, family/lineage, and wealth. By safeguarding these areas, not only does an individual’s life improve, but justice, peace, and balance are also maintained in society. Scholars such as Imam Ghazali, Imam Shatibi, Ibn Taymiyyah, and Shah Waliullah Dehlawi explained the principles of understanding the objectives of Shariah and emphasized that its purpose is not to create hardship or confusion, but to ensure human welfare and peace of mind.